FAKTOR-FAKTOR KETIDAKBERHASILAN IMPLEMENTASI PROGRAM SIDEKEM (SISTEM INFORMASI DESA DAN PEMBANGUNAN KAWASAN PERDESAAN) DI KABUPATEN PEMALANG - Yulia Dwi Rahmawati; Maesaroh Maesaroh; Nina Widowati (Journal of Public Policy and Management Review, 2023)
The implementation of the Village Information System (SID) through SIDEKEM is an innovation program that utilizes information and communication technology to support resource management at the regional and village levels in order to provide free and open village data information. The purpose of this study is to collect data and then analyze what factors have caused the unsuccessful implementation of SID through the SIDEKEM program in Pemalang Regency. The research method used in the research is descriptive qualitative, with data collection techniques of interviews and documentation. The results showed that the factors that caused the unsuccessful implementation of SIDEKEM in Pemalang Regency were the unavailability of specialized human resources who were competent to operate SIDEKEM, the lack of budget and facilities to support SIDEKEM operations, and there were problems of authority disputes in implementation. This has resulted in a very low level of village compliance with the established SOP. Researchers suggest that each village should have a dedicated human resource and DINPERMASDES should improve the quality of human resources through training for village administrators. In addition, impose sanctions on villages that do not implement SIDEKEM so that they can be motivated to meet the standards and objectives of the SIDEKEM program, and maximize the budget for operations in implementing the SIDEKEM program in Pemalang District. In addition, researchers also provide suggestions so that the SIDEKEM program can be reviewed regarding the effectiveness of the program to continue to implement.